Development of The Lupus Clinical Trials Enrollment Decision Aid: a pilot study - Khalili, Leila; Kukafka, Rita; Weiner, Julia; Inzerillo, Sean; Tang, Wei; Geraldino-Pardilla, Laura; Schmidt, Nancyanne; Gartshteyn, Yevgeniyia; Alvarez, Kathleen; Askanase, Anca (Frontiers in Lupus, 2024)
Introduction: In this pilot study, we describe the development of a patient-centered Decision Aid (DA) for participation of SLE clinical trials called “The Lupus Clinical Trials Enrollment DA”. Methods: A draft DA was designed by a development working group using a collaborative, iterative process using the International Patient Decision Aid Standards (IPDAS) guidelines. The approved draft DA was then pilot tested and refined using semi structured interview with 10 lupus providers and 12 SLE patients. Descriptive statistics were calculated. Interviews/surveys were conducted until thematic saturation was achieved. Responses on usefulness were accumulated, and mean usefulness scores were calculated. Feedback from the semi-structured interviews were categorized into several themes as outlined in the results section. Results: The definition of treatments, side effects of each option, and expected improvement from each option was outlined. 90% of providers and 91.7% of patients reported that the definition of SOC treatment was clear. Additionally, the expected improvement for SOC (90% of providers, 100% of patients), clinical trial drug (70%, 91.6%), and placebo (70%,100%) were noted to be clear. Side effects of SOC (80%,100%), clinical trial drug treatment (80%,100%), placebo (90%, 100%), were also noted to be clear. 100% of providers and patients thought that the figure outlining pros/cons of participating in clinical trials was appropriate. The mean usefulness scores for the DA were 4.45/5 for providers and 4.67/5 for patients. Discussion: These data demonstrate that both patients and providers confirm that the newly developed The Lupus Clinical Trials Enrollment DA is useful and easy to use. Qualitative feedback from providers demonstrated concern that aspects of the DA, such as expected improvement and side effects might be unclear to patients; however, patients did not express the same concern in either the quantitative or qualitative feedback.